Colombia: Security as the road to peace? The role of Europe and the international community in the Colombian conflict - Günther Maihold (Stiftung Wissenschaft und Politik (SWP), 2004)
The controversial Colombian program of 'democratic security' appears to be working. And because Colombia's population is also giving the government of President Álvaro Uribe Vélez good marks halfway through its term, the president's efforts to win reelection are gaining new momentum. The number of kidnappings and terrorist attacks in the country fell significantly last year, and the first steps toward solving the decades-long conflict that has rippled throughout the Andes region have been made. Now it is up to the international community. New opportunities are now available for giving the peace process a push by providing it with the kind of support it needs. Europe, with its policy of engagement on behalf of the peace process, has an important role to play in bringing together national and international efforts to resolve Colombia's conflict. However, central questions remain to be clarified with the Colombian government. (SWP Comments / SWP)
Keywords: 320